The Significance of ST Depression in a Postmenopausal Woman on Estrogen Therapy during Regadenoson Myocardial SPECT Imaging - Nishaki Kiran Mehta; Charles Hardebeck; Martha Gulati (Case Reports in Cardiology)
The incidence of false-positive stress tests has been noted in women, especially on hormone replacement therapy. Current literature describes this phenomenon in treadmill and adenosine stress tests. The introduction of regadenoson as a vasodilator agent has been widely adopted owing to its potency and specificity. To our knowledge, false-positive stress test with regadenoson in a postmenopausal woman on estrogen has never been described. Given the higher chronotropic response with regadenoson, we believe that normal perfusion images with a higher heart rate response indicate a good prognosis in such patients.